CO2 mitigation and phycoremediation of industrial flue gas and wastewater via microalgae-bacteria consortium: Possibilities and challenges - Chia S.R.; Chew K.W.; Leong H.Y.; Ho S.-H.; Munawaroh H.S.H.; Show P.L. (Elsevier B.V., 2023)
Algae; Carbon dioxide; Climate change; Flue gases; Flues; Industrial emissions; Nutrients; Operating costs; Petroleum prospecting; Wastewater treatment; CO$-2$/ emission; CO$-2$/ mitigation; Co-culturing; Environmental pollutions; Industrial flue gas; Micro-algae; Microalga-bacteria consortium; Nutrient removal; Phycoremediation; Wastewater treatment, CO2 mitigation; Bacteria